Spain : inter-departmental correspondence - Carthy, A. E.
030-0125-001 TRADES UNION CONGRESS. INTER- DEPARTMENTAL CORRESPONDENCE. From A. E. CARTHY Department International To Mr. E. PARKIN Date 5th July, 1938. SUBJECT. SPAIN Since the beginning of the year, the following is a list of cheques sent to the C.W.S. or Co-op.Union: 17 January "HARTBRIDGE " demurrage 2,050.11.10 37.12. 4 7 February "PLOVER" 2,580. 5. 0 less credit 5.11. 5 2,574.13. 7 9 February Co-op. Union 100. 1. 0 4,762.18. 9 ACCOUNTS NOT PAID, BUT INVOICES RECEIVED. 28 June cod 787.10. 0 29 June soap 210. 0. 0 30 June milk 1,212.10. 0 £ 2,210. 0. 0 There are also on order, but no invoices to hand, 5,600 pairs of children's sandals, and 300 dozen pairs of children's socks approx. cost (probable) £725. 292/946/30/125